Exercício aeróbico na síndrome de sjögren primária: estudo controlado e randomizado - Miyamoto, Samira Tatiyama [UNIFESP] (2016)
Objective: to investigate the effects of a supervised walking program in women with primary Sjögren?s syndrome (pSS). Methods: this randomized controlled trial with intention-to-treat analysis included 45 women fulfilling the American European Consensus Criteria (2002) for pSS. They were randomized into Training Group (GT, n= 23) and Control Group (GC, n= 22). The evaluation tools Functional Assessment of Chronic Illness Therapy Fatigue Subscale (FACIT-Fatigue), Beck Depression Inventory (BDI) and EULAR Sjögren?s Syndrome Patient Reported Index (ESSPRI) were performed prior to intervention (T0), after 8 weeks (T8) and 16 weeks (T16). The EULAR Sjögren?s Syndrome Disease Activity Index (ESSDAI), Medical Outcomes Study 36 (SF-36) and maximal exercise test on the treadmill were performed at T0 and T16. The supervised walking occurred 3 times a week for 16 weeks, from 30 to 60 minutes each session. The intensity of the exercise was based on the heart rate at 80% of the maximum heart rate (HRmax) reached in the treadmill test. Results: Four patients in GT and 2 in GC dropped out during the study. CRP (p= 0,005), CK (p= 0,018), C4 (p< 0,001), VO2max (ml.kg-1.min-1) (p= 0,002), BDI (p= 0,001), vitality (p= 0,003) and role emotional (p= 0,012) domains and mental component summary (p= 0,009) of the SF-36 increased in both groups. FACIT-fatigue (p= 0,042) and distance covered on the test (p= 0,020) improved only in GT. There were no differences over time in the other variables and neither between groups by repeated-measures analysis of variance (ANOVA). The mean change after 16 weeks of VO2max (ml.kg-1.min-1) (p= 0,016), distance (p= 0,043) and FACIT-fatigue (p= 0,030) was higher in the GT than in the GC. There was correlation between the improvement of VO2max (ml.kg-1.min-1) and improvement of FACIT-fatigue (r= 0,418, p= 0,047), physical functioning (r= 0,557, p= 0,006) and general health domains of the SF-36 (r= 0,525, p= 0,010) and physical component summary of the SF-36 (r= 0,478, p= 0,021) in GT. The improvement of fatigue (FACIT-fatigue) in the GT correlated with the improvement of the VO2max (ml.kg-1.min-1) (r= 0,418, p= 0,047), ESSPRI fatigue (r= -0,677, p< 0,001), ESSPRI pain (r= -0,429, p= 0,041), ESSPRI total (r= -0,630, p= 0,001), BDI (r= -0,474, p=0,022), physical functioning (r= 0,682, p< 0,001), role-physical (r= 0,552, p= 0,006), general health (r= 0,423, p= 0,044), social functioning (r= 0,425, p= 0,043) and mental health (r= 0,586, p=0,003) domains of the SF-36 and physical component summary (r= 0,522, p= 0,011) and mental component summary (r= 0,456, p= 0,029) of the SF-36. From the GT, 95,4% of the patients rated themselves as clinically improved versus 62% of the patients in the GC (p= 0,049). The compliance rate for the exercise program sessions averaged 72,4% (21 - 92%). Conclusion: This supervised walking program was demonstrated to be feasible and safe with improvement of the aerobic capacity, exercise tolerance, fatigue and perception of clinical improvement in pSS patients. There were also association between improvement of aerobic capacity and improvement of fatigue and physical component of the quality of life, as well association between improvement of fatigue and improvement of depression and physical and mental components of the quality of life.